2014
DOI: 10.1177/0363546514553089
|View full text |Cite
|
Sign up to set email alerts
|

Labral Reconstruction With Iliotibial Band Autografts and Semitendinosus Allografts Improves Hip Joint Contact Area and Contact Pressure

Abstract: Labral reconstruction appears to improve femoroacetabular joint biomechanics as compared with the labrum-resected state; these improved biomechanics may translate into increased joint function clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 38 publications
1
92
0
Order By: Relevance
“…Strategies of treating labral tears continue to evolve with our understanding of labrum physiology and function. Recent studies imply that the labrum performs an important role in hip stability and decreasing contact stresses across the hip joint [5–8]. The biomechanical case for labral preservation can be made, and outcomes studies are beginning to suggest the same [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies of treating labral tears continue to evolve with our understanding of labrum physiology and function. Recent studies imply that the labrum performs an important role in hip stability and decreasing contact stresses across the hip joint [5–8]. The biomechanical case for labral preservation can be made, and outcomes studies are beginning to suggest the same [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…15 In a previous study, ITB, gracilis, anterior tibialis, and semitendinosus autografts were found to have similar biomechanical properties to the native labrum. 16 However, there is a lack of literature on the intrinsic biomechanical characteristics of commonly used allografts 17 or the surrounding soft tissues (indirect head of rectus femoris and capsule) when used for labral restoration techniques. At our institution, ITB autografts have been used for labral reconstruction with good results at short-term and midterm follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…11 Nepple and colleagues 8 reported a significant increase in hip distractive stability with a partial labral resection state as compared with labral reconstruction. Furthermore, recently published cadaveric biomechanical studies have reported improvements in the joint contact area, intra-articular pressures, 12 and pressurization with both labral repairs and labral reconstructions. 5 Likewise, good results have been reported for labrum reconstruction using ligamentum teres capitis or fascia lata autograft in patients undergoing open surgical hip dislocation.…”
Section: Discussionmentioning
confidence: 99%